STUDI KOMPARATIF HASIL BELAJAR BIOLOGI DIDASARKAN PADA PERSEPSI SISWA TERHADAP IKLIM KELAS (CLASSROOM ENVIRONMENT SCALE/CES): STUDI EX POST FACTO PADA SISWA DI SMAN 1 JAKARTA - Sigit, Diana Vivanti; Putrawan, I Made; Sulfitania, Claudia (Universitas Negeri Jakarta, 2016)
Learning is closely associated in determining student learning outcomes. In the process of teaching and learning, teachers have an important role in the achievement of learning goals. One indicator of achievement learning goals can be seen from the results of student learning outcomes. Teachers belonging to the environmental conditions or climate. Student’s perceptions of classroom climate greatly affect student learning outcomes. The purpose of this research was to determine differences in biology of learning outcomes based on student’s perceptions of classroom climate (Classroom Environment Scale/CES). This research was held in 1 High School Jakarta on April-May 2016. This type of research was quantitative with ex post facto method through comparative studies. The subjects of research were students of class X IPA with a total sample of 54 students were selected by Simple Random Sampling. Data collection techniques by using achievement test biological and Classroom Environment Scale (CES). The analysis prerequisite test was used the test for normality with the Kolmogorov-Smirnov test and homogeneity test with F-test. Based on the calculations, data were normally distributed and homogeneous. Hypothesis testing was done through t-test. The results of the t-test for biology learning outcomes shows that there was differences between biology learning outcomes both positive and negative student’s perceptions of classroom climate (Classroom Environment Scale/CES).